2021
DOI: 10.22392/actaquatr.757088
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Requirements of Larval Simuliidae (Insecta, Diptera) Species of some Streams in Camili Valley (Artvin, Turkey)

Abstract: This study was carried out in July 2016 in Camili (Macahel) which is Turkey's first and only biosphere reserve area. This study aimed to investigate the Simuliidae species of some streams in Camili Valley, to identify the "reference site" which are important for the Water Framework Directive (WFD), to determine ecological characteristics of the studied sites according to System A and System B Classification of Water Framework Directive (WFD), to explore the relationship between the recorded species and some en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The finding of our study proved that the existence of blackfly in West Bank region and the finding of our study align with the pervious study which indicate that these species breeding in fast-flowing freshwater habitats furthermore, the study found that the species breeding in water exhibit high oxygen level, alkaline water and elevated temperatures, consistent with pervious research [13][14][15][16][17][18].…”
Section: Larval and Adult Habitatsupporting
confidence: 91%
“…The finding of our study proved that the existence of blackfly in West Bank region and the finding of our study align with the pervious study which indicate that these species breeding in fast-flowing freshwater habitats furthermore, the study found that the species breeding in water exhibit high oxygen level, alkaline water and elevated temperatures, consistent with pervious research [13][14][15][16][17][18].…”
Section: Larval and Adult Habitatsupporting
confidence: 91%